Evolution of Feed Forward Network for solving Classification and Prediction Problems - Sornam, M; Balamurugan, P (International Journal of Computer Sciences and Engineering, 2025)
Over the past decade, ANN is used in many fields including Engineering and Medical electronics. ANN is also been applied to solve many problems of classification and prediction. Depending on the problem space and complexity various approaches were proposed to solve the problems in an efficient way. Multi-layer Feed forward network is one of the network architecture predominantly used to solve classification and prediction problems. The objective of this paper is to study the various methods available in the literature for solving those problems. The study starts with a simple feed forward network for image classification, then continued to investigate the methods to improve the classification accuracy using various wavelets and dimensionality reduction techniques. The various improvements were proposed for Backpropagation algorithm including complex BP were analysed. For performance improvement, methods of evolutionary algorithms and Pruning techniques were studied briefly. Finally the improved RBF network for complex numbers was analysed. This paper gives an overall idea of how the feed forward network was evolved with various approaches for solving classification and prediction problems